Image-making-India visual culture, technology, politics - Favero, Paolo S. H. 1969- (Routledge, 2021)
"Building upon long-term ethnographic research among image-makers in Delhi, Mumbai and other Indian cities, the author interrogates the dialogue between visual culture, technology and changing notions of political participation. The book explores selected artistic experiences in documentary and fiction film, photography, contemporary art and digital curation that have in common a desire to engage with images as tools for social intervention. These experiences reveal images' capacity not only to narrate and represent but also to perform, do and affect. Particular attention is devoted to the 'digital', a critical landscape that offers an opportunity to re-examine the significance of images and visual culture in a rapidly changing India. This volume will be of particular interest to scholars of visual and digital anthropology and cultures as well as South Asian studies"--